Assessing the effect of pregnancy intention at conception on the continuum of care in maternal healthcare services use in Bangladesh: Evidence from a nationally representative cross-sectional survey. - Md Nuruzzaman Khan; Melissa L Harris; Deborah Loxton (PLoS ONE, 2020)
Background The Continuum of Care (CoC; defined as accessing the recommended healthcare services during pregnancy and the early postpartum period) is low in lower-middle-income countries (LMICs). This may be a major contributor to the high rates of pregnancy-related complications and deaths in LMICs, particularly among women who had an unintended pregnancy. With a lack of research on the subject in Bangladesh, we aimed to examine the effect of unintended pregnancy on CoC. Methods Data from 4,493 mother-newborn dyads who participated in the cross-sectional 2014 Bangladesh Demographic and Health Survey were analysed. Women's level of CoC was generated from responses to questions on the use and non-use of three recommended services during the course of pregnancy: four or more antenatal care (ANC) visits, skilled birth attendance (SBA) during delivery, and at least one postnatal care (PNC) visit within 24 hours of giving birth. Global recommendations of service use were used to classify CoC as high (used each of the recommended services), moderate (used at least two of the three recommended services), and low/none (no PNC, no SBA, and ≤3 ANC visits). Women's pregnancy intention at the time of conception of their last pregnancy (ending with a live birth) was the major exposure variable, classified as wanted, mistimed, and unwanted. Unadjusted and adjusted (with individual-, household-, and community-level factors) multilevel multinomial logistic regression models were used to assess the association between unintended pregnancy and level of CoC. Results In Bangladesh, the highest level of CoC occurred in only 12% of pregnancies that ended with live births. This figure was reduced to 5.6% if the pregnancy was unwanted at conception. The antenatal period saw the greatest drop in CoC, with 65.13% of women receiving at least one ANC visit and 26.32% having four or more ANC visits. Following the adjustment of confounders, an unwanted pregnancy was found to be associated with 39% and 62% reduced odds of women receiving moderate and high levels of CoC, respectively, than those with a wanted pregnancy. Having a mistimed pregnancy was found to be associated with a 31% reduction in odds of women achieving a high CoC than women with a wanted pregnancy. Conclusion Almost nine in ten women did not achieve CoC in their last pregnancy, which was even higher when the pregnancy was unintended. Given that the ANC period has been identified as a critical time for intervention for these women, it is necessary for policies to scale up current maternal healthcare services that provide in-home maternal healthcare services and to monitor the continuity of ANC, with a particular focus on women who have an unintended pregnancy. Integration of maternal healthcare services with family planning services is also required to ensure CoC.